Sex differences in allostatic load trajectories among midlife and older adults: Evidence from the China health and retirement longitudinal study. - Guannan Li; Gindo Tampubolon; Asri Maharani; Chenglin Tu (PLoS ONE)
The female advantage in life expectancy sits uneasily with female disadvantage in health and well-being in later life compared to their male counterparts. This health disparity has been suggested to rest on sex difference in allostatic load (AL). We aim to delineate the sex-specific age trajectories of AL among midlife and older adults in China and to interpret the contradiction between the female advantage in life expectancy and their disadvantage in health in later life from the perspective of physiological dysregulation. Using data from the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2011 and 2015, we included 3,836 male and 3,308 female Chinese adults aged 45 and older. Two-level mixed-effects models were fitted to examine how AL changed over time. Missing values were addressed by performing multiple imputations using chained equations. Results show AL increases with age for both sexes, with a steeper rise in females and a slight decline in males after adjusting for the sex-age interaction. Older males born before the People's Republic of China (PRC) exhibited different AL trajectories from younger cohorts. The sex-specific trajectories converge around the late 60s, with females surpassing males, aligning with the life expectancy-health paradox. The presence of a healthier older male cohort in CHARLS suggests future studies should account for cohort effects.